AN EXAMINATION OF PHYSICAL DISTANCING AMIDST COVID-19 AND ITS IMPACT ON ACADEMIC CONFERENCES IN NIGERIA - Nwobi, Uchechukwu Anthony (African Journal of Social and Behavioural Sciences, 2021)
The study is an examination of physical distancing regime following Covid-19 pandemic and its impact on academic conferences in Nigeria. The rapid spread of the corona virus ravaging the world led to the adoption of physical distancing policy as a strategy to curtail its spread. That equally led to the disruption and interruption of academic activities as well as face-to-face conferences while virtual academic conferences became the norm. It is from the foregoing that the objectives of this study were drawn. Specifically, the study is to ascertain the extent to which physical distancing amidst covid-19 has reduced the rate of physical relationship-based academic conferences. Investigate the extent to which physical distancing amidst covid-19 has reduced accessibility of academic conferences and find out the extent to which physical distancing amidst covid-19 has reduced attention and time span of academic conferences. The secondary sources of data were used namely journals, textbooks, newspapers, web pages, and government publications. To complement that, the electronic interview was also used. Inter-group threat theory was adopted for the discourse. It was found that there was a reduced physical relationship-based academic conference; access to conferences was reduced due to unstable power supply and internet services. Attention and time span were reduced. The study recommends the enhancement of partnership building among participants. Capturing of participants attention in the first eight seconds and new stimulus introduced every few seconds of the interactions.